Potential Method in the Limit Problems for the Processes with Independent Increments - Bratiichuk, N. S. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We propose a new approach to the application of the Korolyuk potential method for the investigation of limit functionals for processes with independent increments. The formulas for the joint distribution of functionals related to crossing a level by the process are obtained and their asymptotic analysis is performed. The possibility of crossing a level by the process in a continuous way is also investigated.